Asteroid 2024 YR4: A Comprehensive Review - Salem, Mohamed Khalil; Osman, Hesham; El Ashkar, Alaa (International Journal of Advanced Astronomy, 2025)
Asteroid 2024 YR4, a recently discovered near-Earth object (NEO), has captured considerable attention due to its unique orbital characteristics and potential implications for planetary defense strategies. This review paper aims to provide a comprehensive analysis of Asteroid 2024 YR4, focusing on its discovery, orbital properties, physical attributes, and the implications for future research and impact risk assessment. This study highlights the importance and the critical role of coordinated global efforts in monitoring the asteroid. Our study underscores the need for sustained funding in asteroid tracking systems to address future risks and enhance our understanding of NEO dynamics.